Embodied Collective Choreographies: Listening to Arena Nightclub’s Jotería Sonic Memories - Alvarez Jr., Eddy Francisco (Performance Matters, 2022)
Merging sound studies, performance studies, and jotería studies, this essay documents sonic moments and memories of 1990s Los Angeles at Arena, a nightclub frequented by queer Latinx youth. Building on Alexandra Vasquez's "listening in detail" and Karen Tongson's "queerly listening," the author argues that jotería listening is an auditory practice and methodology employed by queer Latinx communities engaged in world-making strategies. Through jotería listening, we are able to hear sonic memories of Arena, which map moments of collectivity, community building, experimentation and resistance against hostilities encountered by jotería youth in LA in the 1990s. Highlighting three soundmarks or recognizable sounds—whistles, foot-stomping, and clapping—and their meanings, this essay maps corporeal and embodied performances of self and community as it documents critical moments in jotería histories of nightlife in Los Angeles.